Sinapic Acid and Its Derivatives as Medicine in Oxidative Stress-Induced Diseases and Aging. (10th November 2015) - Chen, Chunye
Abstract : Sinapic acid (3, 5-dimethoxy-4-hydroxycinnamic acid) is an orally bioavailable phytochemical, extensively found in spices, citrus and berry fruits, vegetables, cereals, and oilseed crops and is known to exhibit antioxidant, anti-inflammatory, anticancer, antimutagenic, antiglycemic, neuroprotective, and antibacterial activities. The literature reveals that sinapic acid is a bioactive phenolic acid and has the potential to attenuate various chemically induced toxicities. This minireview is an effort to summarize the available literature about pharmacokinetic, therapeutic, and protective potential of this versatile molecule in health related areas.